Discourse Network Analysis of Betrayal News Regarding the Presidential Candidate of the Coalition for Change and Improvement on Kompas.com - Pitoyo Pitoyo; Bella Amalia (Ikatan Sarjana Komunikasi Indonesia, 2024)
Political communication is heating up as the 2024 Indonesian Presidential Election approaches. Nine political parties in the Indonesian Parliament (DPR RI) have formed three coalitions: Change and Improvement (Nasdem, Democrat, PKS), Indonesia Maju (Gerindra, Golkar, PAN, PKB), and PDIP (PDI-P, PPP). However, in late November 2023, a sudden shift occurred when Nasdem and PKB supported Anies Baswedan and Muhaimin Iskandar (Amin). The Democratic Party felt betrayed. This research aims to analyze political parties' communication with the emergence of presidential and vice presidential candidates Amin on kompas.com. Researchers examined the communication network digitally using discourse network analysis (DNA). This method used the DNA approach in the context of political communication concepts proposed by Nimmo, including the Communicator, Message, Communication Channel, Audience, and Effect. These five concepts serve as the foundation for analyzing news related to the accusations of betrayal in the Change and Improvement coalition. This research conducts qualitative analysis, providing a depiction of the digital communication lines between communicators within the political party coalitions, especially those most frequently accusing the Amin coalition of betrayal, and rebuttals from the parties accused of betrayal.